Hypoglycemia in Geriatric Patients with Diabetes: A Review - Untari, Eka Kartika; Yuswar, Muhammad Akib (Pharmaceutical Journal of Indonesia, 2024)
Background: The prevalence of diabetes tends to be high, 42% of geriatric patients admitted havea diabetes diagnosis, and 33% of these patients experience hypoglycemia. Hospitalization isnecessary for diabetic elderly individuals because their blood glucose levels make themmore vulnerable to other complications. The incidence of hypoglycemia in geriatric patients maybe caused by a variety of factors, including polypharmacy, pharmacokinetic andpharmacodynamic changes, hormonal regulation disorders, food and water intake disturbances,decreased intestinal absorption, and cognitive disorders, as well as other organ disorders that causedisruption of the ability to metabolize antihyperglycemia.Methods: This review will go over how frequently geriatricians, especially those withdiabetes, develop hypoglycemia as a result of using anti-diabetics or other medications thatlead to drop blood sugar.Results: Sulfonylurea and insulin groups are the most frequent causes of hypoglycemia indiabetic older people, according to the articles we analyzed. The significance of specific carefor the elderly population in order to lessen the effects of hypoglycemia.Conclusions: For geriatric individuals with DM, routine blood glucose monitoring is advisedto prevent diabetic complications.